A new Pan African polyspecific antivenom developed in response to the antivenom crisis in Africa. - Laing, G; Renjifo, J; Ruiz, F; Harrison, R; Nasidi, A; Gutierrez, J; Rowley, P; Warrell, D; Theakston, R (2003)
Currently there is a crisis in the supply of antivenom for treatment of snake bite in sub-Saharan Africa. Commercial pressures have resulted in the reduction or even cessation of production of antivenom by European manufacturers while continued production of antivenom in Africa has been threatened by the privatisation of the only remaining company based in Africa. As a consequence, there has been an increase in snake bite morbidity and mortality in many African countries. Two Latin American antivenom manufacturers have agreed to produce antivenom suitable for Africa, using venoms from the species which are of the greatest medical importance in sub-Saharan Africa. Preclinical in vivo assays of neutralising potency demonstrated that a new Pan African antivenom produced in Colombia compared favourably with the existing commercial monospecific and polyspecific antivenoms. This new antivenom, and a similar product being manufactured in Costa Rica, are now candidates for clinical testing at an appropriate site in Africa.